Root canal reconstruction using biological dentin posts: A 3D finite element analysis - Seda Falakaloğlu; Özkan Adıgüzel; Gökhan Özdemir (Tabriz University of Medical Sciences, 2019)
Background. Several types of post have been developed for clinical use. A biological dentin post obtained from an extracted tooth eliminates the problems arising from material differences and reduces the fracture rate in teeth undergoing root canal treatment. This study used finite element analysis to compare a biological dentin post with posts made of two different materials. Methods. Three 3D models of the upper central incisor were created, and stainless-steel, glass fiber and biological dentin posts were applied to these models. The restoration of the models was completed by applying a composite as the core structure and a ceramic crown as the superstructure. Using finite element stress analysis in the restoration models, a 100-N force was applied in the vertical and horizontal directions and at a 45º angle, and the suitability of the biological dentin post was evaluated by comparing the data. Results. Under the applied forces, the greatest stress accumulation was seen in the models with the stainless steel post. Because the stainless steel post was more rigid, stress forces accumulated on the surface instead of being transmitted to the tooth tissue. In the models with the glass fiber and biological dentin posts, the post material responded to the stratification in tandem with the dental tissue and did not cause excessive stress accumulation on the tooth or post surfaces. Conclusion. The results showed that biological dentin posts prevent the accumulation of stresses that might cause fractures in teeth undergoing root canal treatment. In addition, the physical compatibility and biocompatibility of a biological dentin post with the tooth imply that it is a good alternative to the types of post currently used.